The transacting factor CBF-A/Hnrnpab binds to the A2RE/RTS element of protamine 2 mRNA and contributes to its translational regulation during mouse spermatogenesis. - Nanaho Fukuda; Tomoyuki Fukuda; John Sinnamon; Abrahan Hernandez-Hernandez; Manizheh Izadi; Chandrasekhar S Raju; Kevin Czaplinski; Piergiorgio Percipalle (PLoS Genetics, 2013)
During spermatogenesis, mRNA localization and translation are believed to be regulated in a stage-specific manner. We report here that the Protamine2 (Prm2) mRNA transits through chromatoid bodies of round spermatids and localizes to cytosol of elongating spermatids for translation. The transacting factor CBF-A, also termed Hnrnpab, contributes to temporal regulation of Prm2 translation. We found that CBF-A co-localizes with the Prm2 mRNA during spermatogenesis, directly binding to the A2RE/RTS element in the 3' UTR. Although both p37 and p42 CBF-A isoforms interacted with RTS, they associated with translationally repressed and de-repressed Prm2 mRNA, respectively. Only p42 was found to interact with the 5'cap complex, and to co-sediment with the Prm2 mRNA in polysomes. In CBF-A knockout mice, expression of protamine 2 (PRM2) was reduced and the Prm2 mRNA was prematurely translated in a subset of elongating spermatids. Moreover, a high percentage of sperm from the CBF-A knockout mouse showed abnormal DNA morphology. We suggest that CBF-A plays an important role in spermatogenesis by regulating stage-specific translation of testicular mRNAs.